Strategi Holding Company Dalam Melaksanakan Tanggung Jawab Sosial Perusahaan (Jurnal Ilmu Kesejahteraan Sosial, 2018)
The one form of corporate intervention in development is implemented into Corporate Social Responsibility (CSR). In the last ten years, the number of corporate that implement CSR is getting increase. However, there are not many holding companies that implement CSR comprehensively and make CSR as part of the company’s strategy. This research describes the CSR strategy at holding company PT Astra International which is implemented comprehensively and internalized in the overall activity of the company with qualitative method. The results of the research shows that one of the implementation of these strategies is the implementation of community development program with empowerment approach, as one method in the effort to achieve social welfare with Kampung Berseri Astra program. The uniquenesses of CSR strategy in holding company is goal, vehicles, measurement, benefactors, benefits, and time frame of implementation CSR that related with bussiness unit, also become part of the company’s business strategy